Analisis Strategi PT Pakuwon Jati Tbk - Putri, Made Wulan Ranjani Yunantara; Murhadi, Werner R. (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research analyzes the management strategy of PT Pakuwon Jati Tbk, this company is one of the largest property developers in Indonesia. This research evaluates company performance through external analysis which includes PESTEL and Porter's Five Forces and internal analysis which includes value chain and SWOT. This research uses strategic tools in analysis, namely the TOWS Matrix, Space Matrix, IE Matrix, and BCG Matrix as well as the Grand Strategy Matrix to then draw strategic priority decisions using QSPM. The results show that Pakuwon is in a strategic position to capitalize on opportunities in the growing property market with superblock innovation and a focus on sustainability. The recommended strategy is market development to expand the reach of the lower middle segment through cost efficiency and innovative design, as well as product development to increase competitiveness through technology integration. It is hoped that the implementation of this strategy can strengthen Pakuwon's position in the property industry and increase its economic contribution in Indonesia.